PEDAGOGICAL CONDITIONS FOR CREATIVITY IMPROVEMENT ACQUIRING STUDY COURSE CLOTHING DESIGN AND MODELLING - Jelisejeva, Natalia; Mezinska, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The situation in modern education has new demands for university students. To be competitive in labor market nowadays professional knowledge is not enough, students have to develop personality that as far as possible indicates individuality and creative potential. Creativity relates to the ability to perceive the different, readiness for innovation, creative worldview. In order to achieve this target, pedagogical conditions that ensure creativity and motivates for creative world perception are necessary. Pedagogical conditions that foster creativity level: the organization of productive student work and informative - communicative technologies.